Women's Experiences of Intimate Partner Violence While Incarcerated: The Measurement Structure, Reliability, and Validity of a Novel Instrument - Garthe, Rachel C. (Violence against women, 2024)
While incarcerated, women may continue to experience intimate partner violence (IPV), perpetrated by partners who reside in the outside community. Power and control dynamics of abusive relationships may intensify as the abuser exploits their partners’ incarceration. The current study assessed IPV experiences of 832 incarcerated women (50% white, 76% mothers), testing a novel instrument. Results validated a two-factor structure: (a) general abuse (i.e., verbal, physical) and (b) deny or threaten to deny (i.e., leveraging the women's incarceration to intimidate or control). This study introduces a novel instrument to measure IPV while incarcerated and provides implications for research and practice.